Management of Acute Soft Tissue Injuries of the Cheek and Principles of Scar Revision - Hudson, Caroline; Olson, Krista (Facial Plastic Surgery, 2021)
Facial soft tissue injury is a challenging and complex problem for the facial plastic and reconstructive surgeon for cosmetic and functional reasons. This article will focus on the management of soft tissue injuries of the cheek, one of the most important presenting areas of the face. The cheek, like any other part of the face, is susceptible to several types of injury and any of these injuries have the potential to disfigure and debilitate. Knowledge of anatomical structures and wound healing principles is critical to devising an appropriate management plan and achieving superior patient outcomes in scar revision cases. Multiple techniques to improve long-term scarring from facial soft tissue injuries are available.
Keywords: scar revision; facial trauma; acute soft tissue trauma; facial plastic and reconstructive surgery